Learning Model based on Multiple Intelligences oriented towards Higher Order Thinking Skills (HOTS) through the application of Visual, Auditory, Read-Write Preferential, Kinesthetic (VARK), and Directed Reading Listening Thinking Activity (DRLTA) in Elementary School - Suhartono Suhartono; Hanafi Hanafi; Cici Murniasih; Moch. Noviadi Nugroho (UM Purwokerto Press, 2025)
The purpose of this study was to develop a learning model based on multiple intelligences and students' critical thinking skills through visual, auditory, preferential read-write, kinesthetic (VARK) learning strategies, and the application of the directed reading listening thinking activity (DRLTA) model to elementary school students. The stages include: 1) formulating research problems and determining survey objectives, 2) determining concepts and hypotheses and digging literature, 3) sampling, 4) making kueisoner, 5) field work, 6) data processing, 7) analysis and reporting. The result of the need assessment score is 3.54, the product development stage, FGD, expert and practitioner validation and the field trial stage. The feasibility of this model is tested based on: 1) The assessment of psychologists is assessed based on three aspects, namely the elements of the supporting theory used, the elements of the learning stages and the elements of the implementation of learning techniques to get a score of 4.77 or including